Microbial niche differentiation and agronomic performance of diseased Capsicum annuum - Yang, Zhiqi; Wang, Yankun (Frontiers in Microbiology, 2025)
IntroductionPlant–microbial interactions shape the plant microbiome, leading to niche differentiation in microbial communities. The dynamic variation in beneficial and phytopathogenic microbes from different niches (including the roots, stems, leaves, and rhizosphere soil (RS) of plants) is poorly understood.MethodsHigh-throughput sequencing was performed to explore the shifts in microbial community composition in different niches of diseased and healthy long line peppers (LLPs, Capsicum annuum L.). Correlations between microbial community composition and agronomic performance were analyzed to speculate the presence of potential pathogens and beneficial microbes in different niches and their effects on LLPs.ResultsThe relative abundance of microbial communities in the LLP different niches was dynamic. Some microbes exhibited significantly negative effects on the LLP growth and fitness, including the genera bacterial Pseudomonas, Pectobacterium and fungal Fusarium, Alternaria, Xepicula, Mrakia, and Verrucoconiothyrium. Two pepper-wilt fungi F. proliferatum and F. oxysporum were identified according to Koch’s rule, validating the study’s conclusions. The pepper disease reduced plant fresh weight by 72% and increased Fusarium abundance by 2-fold, additionally, LLP plant height, concentrations of leaf chlorophyll a, fruit vitamin C and fresh weight were significantly decreased contrast to healthy plants. Certainly, potential beneficial microbes (e.g., the Priestia, Occallatibacter, and Enterobacter bacteria as well as the Sporobolomyces, Hannaella, Verticillium, Bisifusarium, and Vishniacozyma fungi) significantly promoted some agronomic parameters of LLPs.ConclusionThese finding suggested that various pathogens might be associated with pepper disease symptoms. This study lays a foundation for isolations, identifications, experimental validation of phytopathogens and beneficial microbes.